Food and feeding habits of Otolithes cuvieri (Trewavas, 1974) from Ratnagiri, Maharashtra - Sandhya, K. M.; Chakraborty, S. K.; Jaiswar, A. K.; Shah, Tasaduq Hussain (Indian Journal of Fisheries, 2014)
The present report on food and feeding habits of Otolithes cuvieri is based on the examination of gut contents of 781 fishes within the size range of 83-300 mm collected from Ratnagiri, Maharashtra. Based on index of relative importance values, crustaceans like Acetes spp. and penaeid prawns were found to be the dominant food items followed by fishes, cephalopods and gastropods. Crustaceans were predominant in most of the months. Fishes of smaller lengths preferred only Acetes spp. Dominance of empty stomachs in most of the months as well as in different size groups indicates low feeding intensity of the species